A NEW STRAIGHT-CHAIN HYDROCARBON BIOMARKER ASSOCIATED WITH ANAEROBIC METHANE CYCLING - Thiel V.; Schmale O.; Michaelis W.; Peckmann J.; Reitner J. (My University, 2001)
13C-depleted E and Z n-tricos-10-enes are prominent biomarkers in an anaerobic microbial mat at Black Sea methane seeps. These n-alkenes co-occur with archaeal irregular C25 isoprenoid hydrocarbons, namely 2,6,10,15,19-pentamethylicosane (PMI) and -enes (PMIΔ). Low δ13C-values (−73 and −77‰) for n-tricosenes and PMI imply the anabolism of methane carbon by their source biota. The n-tricosenes apparently originate from microorganisms closely associated with, if not identical to isoprenoid-producing, methane-metabolizing Archaea. Methane-seep deposits of Tertiary to Jurassic ages showed the absence of n-tricosenes, but 13C-depleted n-tricosane (δ13C as low as −87‰), a plausible diagenetic product, was observed in enhanced concentrations in 7 out of 9 samples studied. It is proposed that a preference of n-tricosane over the enveloping n-alkanes may provide a specific hydrocarbon fingerprint for the anaerobic cycling of methane in ancient settings.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская